PEMANFAATAN KERTAS ORIGAMI SEBAGAI MEDIA PEMBELAJARAN DALAM MENGEMBANGKAN KREATIVITAS PADA ANAK USIA 5-6 TAHUN - Ega Oktari; Aunurrahman Aunurrahman; Dian Miranda (Universitas Tanjungpura, 2022)
The research method used is descriptive in the form of qualitative research. The data sources of this study were children aged 5-6 years in RA Baitul Kindergarten Juma'ah and the data obtained in the form of words. The results of data analysis show that the planning and implementation carried out by the teacher structurally good because it is seen from the development of each child's creativity the day is getting better and showing results even though not optimally and there are some children are creative according to what they want to create on the origami paper, It can be seen from the enthusiasm of students in doing folding game activities origami, judging by the children's interest in the origami folding game which is very enthusiastic. Indeed, not all children have the same passion and interest, but most of them are good at playing origami folding, because it can be seen from the children's creativity in creating shapes from paper, imitating simple paper folding, as well as imitate paper folding variations (combinations). Apart from that, some children can doing origami folding activities by not imitating the work of his friends alone and can follow orders given by the teacher, but some children the development has not yet appeared, this can be seen from the child not being able to develop from the example givenby the teacher during the folding activity.